Od cudownego dziecka do mistrzostwa, czyli o znaczeniu interakcji wieloczynnikowej twórczości Wolfganga Amadeusza Mozarta = From a child prodigy to the championship, that is about meaning of multifactorial interaction in the artistic works of Wolfgang Amadeus Mozart - Magda-Adamowicz, Marzenna (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
In the text they concentrated on the active participation in the musical culture, that is on for her creating, based on the musical artistic works of Wolfgang Amadeus Mozart. By way of introduction a notion was discussed artistic work, his acrobatics, climbs and nature of system theories of the artistic work was shown. Against this background a course of the championship of musical Wolfgang Amadeusz Mozart and meanings were portrayed for this of his home environment.
Keywords: Mozart, Wolfgang Amadeusz (1756-1791); Mozart, Wolfgang Amadeus (1756-1791); muzyka; twórczość; music; artistic work